(untitled) (Journal of Technology and Operations Management, 2016)
E-marketing is a crucial factor in the development of an export market for many organizations; it helps the firms to enhance their export performance in order to grab maximum international market share. Moreover, to validate the effectiveness of e-marketing, the current study will investigate the impact of technological factors on the export performance of the firms in developing countries. Though, use of e-marketing is widely spreading around the world but still several e-marketing tools have not been implemented properly that can contribute in many ways to achieve firm performance in terms of increased global market share and operational efficiencies. E-marketing has appeared to be one of the essential factors in maintaining the competitive advantage for any company despite of its size. In this study, TOE (Technology-Organization-Environment) framework has been established to see the impact of following predictors, which are: Technology Orientation; Top Management Support; Pressure from trading partners; and E-marketing adoption of the firm exports performance. The proposed framework has been developed to guide future study in exploring e-marketing technologies. Moreover, this framework can be enhanced by adding other variables and to check firm performance not only by means of exports but also at domestic level. In future, the proposed framework and research model will be empirically validated by administering a survey questionnaire among Firms in a number of developing countries. However, the current study will contribute by filling the gap in the literature and will deliver a clear deliberation for technology adoption of e-marketing to enhance firm export performance.